Sustainable Economic Innovation in MSMEs through the Integration of Digital Technology and Environmentally Friendly Business Practices in Indonesia - Saputra, Tri Oktaviandi; Minarni, Minarni (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This article examines how sustainable economic innovation in Micro, Small, and Medium Enterprises (MSMEs) can be achieved through the integration of digital technologies and environmentally friendly business practices. This topic is essential as MSMEs face increasing pressure to transition toward green economies and adapt to rapid global digital transformation. Background Problems: The primary issue addressed is how MSMEs can enhance competitiveness and sustainability through the synergy of digitalization and green practices, leading to the research question: "How can the integration of digital technologies and environmentally friendly practices drive sustainable economic innovation in Indonesian MSMEs?" Research Methods: A qualitative library research method was employed by reviewing scientific articles, institutional reports, government regulations, and relevant literature published between 2015 and 2024. Thematic synthesis was used to identify conceptual linkages between digitalization, environmental practices, and MSME sustainability. Findings/Results: The study finds that digital technologies—including e-commerce, digital payments, cloud computing, IoT, and data analytics enhance operational efficiency and market reach. When combined with green practices such as energy efficiency, waste reduction, and sustainable material use, MSMEs achieve higher productivity, resilience, and long-term competitiveness. Conclusion: The integration of digitalization and green business practices represents a crucial strategy for advancing sustainable economic innovation in MSMEs. The findings imply the need for pentahelix collaboration and supportive policy frameworks to accelerate MSME transformation toward low-carbon, adaptive, and inclusive business models.